Pollen-inferred regional vegetation patterns and demographic change in Southern Anatolia through the Holocene. (May 2019) - Woodbridge, Jessie; Roberts, C Neil; Palmisano, Alessio; Bevan, Andrew; Shennan, Stephen; Fyfe, Ralph; Eastwood, Warren J; Izdebski, Adam; Çakırlar, Canan; Woldring, Henk; Broothaerts, Nils; Kaniewski, David; et al.
Southern Anatolia is a highly significant area within the Mediterranean, particularly in terms of understanding how agriculture moved into Europe from neighbouring regions. This study uses pollen, palaeoclimate and archaeological evidence to investigate the relationships between demography and vegetation change, and to explore how the development of agriculture varied spatially. Data from 21 fossil pollen records have been transformed into forested, parkland and open vegetation types using cluster analysis. Patterns of change have been explored using non-metric multidimensional scaling (nMDS) and through analysis of indicator groups, such as an Anthropogenic Pollen Index, and Simpson's Diversity. Settlement data, which indicate population densities, and summed radiocarbon dates for archaeological sites have been used as a proxy for demographic change. The pollen and archaeological records confirm that farming can be detected earlier in Anatolia in comparison with many other parts of the Mediterranean. Dynamics of change in grazing indicators and the OJCV ( Olea, Juglans, Castanea and Vitis ) index for cultivated trees appear to match cycles of population expansion and decline. Vegetation and land use change is also influenced by other factors, such as climate change. Investigating the early impacts of anthropogenic activities (e.g. woodcutting, animal herding, the use of fire and agriculture) is key to understanding how societies have modified the environment since the mid–late Holocene, despite the capacity of ecological systems to absorb recurrent disturbances. The results of this study suggest that shifting human population dynamics played an important role in shaping land cover in central and southern Anatolia.